Electric flux fibers with spherical antiferromagnetic approach with electroosmotic velocity - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2022)
In this study, we investigate new type of spherical electromagnetic flow Sa-density of Sa-optical fibers. Then, we give some different conditions for optical spherical electric flux in antiferromagnetic model. Moreover, we investigate some results for electrical flow antiferromagnetic microscale for Lorentz force by electroosmotic velocity. Finally, optical electromagnetic S alpha-phase of spherical S alpha-fluids is performed in homogeneous magnetic Sa-fluid fibers by optical results with antiferromagnetic approach.
Keywords: Spherical frame; S alpha-density; Antiferromagnetic spin; Geometric S alpha-optical fibers; Antiferromagnetic microscale